Utilización del mapa mental como herramienta de ayuda para la toma de decisiones vocacionales - Caballero Hernández-pizarro, Mª Ángeles; Escobar Fernández, Mª Criptana; Ramos Alía, Justo (Revista Complutense de Educación, 2006)
Decision – making process is the core of career guidance. It is, in fact, a very complex process for our students, specially during adolescence. In a research developed by a group of teachers from the Faculty of Education (University Complutense of Madrid), mental maps were introduced in order to help students in this important process. The use of this tool was integrated in a career guidance program. The experience was developed in an experimental group of secondary students (17 students) aged 15, belonging to a High School in Madrid (IES “S. Nicasio”).